Pengaruh Kepemimpinan dengan Kinerja Perawat di Rumah Sakit Pertamina Bintang Amin Kota Bandar Lampung - Dwiky Dermawan Santari; M. Arifki Zainaro; Dewi Kusumaningsih (Malahayati Nursing Journal, 2022)
ABSTRACT Performance is a world issue today. This happens as a consequence of the community's demands for the need for excellent service or high quality services that are inseparable from standards, because performance is measured based on standards. Inpatient Room Pertamina Bintang Amin Hospital by conducting a pre-survey of 15 nurses by conducting free interviews and filling out questionnaires related to leadership and job design, 9 nurses (60%) stated that the leadership and job design at Bintang Amin Hospital were not good, while 6 nurses (40%) of them said it was good. To find out the influence of leadership and job design on the performance of nurses at Pertamina Bintang Amin Hospital, Bandar Lampung City in 2022. This type of research uses quantitative, analytical survey research design with a cross sectional approach. The population and sample in this study were nurses at Pertamina Bintang Amin Hospital Bandar Lampung 103 nurses and used the slovin formula so that n = 81.9 respondents were rounded up to 82 respondents, the sampling technique used purposive sampling. Data analysis using univariate and bivariate using chi square. Most of the nurse leadership in the poor category. Most of the job designs in the poor category. Most of the nurses' performance in the poor category. The results of data analysis using the chi square test obtained a p-value = 0.000 ( 0.05), which means that there is a leadership relationship with the performance of nurses at Pertamina Bintang Amin Hospital. The results of data analysis using the chi square test obtained p-value = 0.000 ( 0.05), which means that there is a relationship between job design and nurse performance at Pertamina Bintang Amin Hospital. Keywords : Leadership, Nurse Performance, Hospital ABSTRAK Kinerja (performance) menjadi isu dunia saat ini. Hal tersebut terjadi sebagai konsekuensi tuntutan masyarakat terhadap kebutuhan akan pelayanan prima atau pelayanan yang bermutu tinggi yang tidak terpisahkan dari standar, karena kinerja diukur berdasarkan standar. Ruang Rawat Inap Rumah Sakit Pertamina Bintang Amin dengan melakukan prasurvey terhadap 15 perawat dengan melakukan wawancara bebas dan pengisian kuesioner terkait kepemimpinan dan desain pekerjaan didapat 9 perawat (60%) pelaksana menyatakan jika kepemimpinan dan desain pekerjaan yang ada di Rumah Sakit Bintang Amin kurang baik, sedangkan 6 perawat (40%) diantaranya menyatakan baik. Diketahui pengaruh kepemimpinan dan desain pekerjaan dengan kinerja perawat di Rumah Sakit Pertamina Bintang Amin Kota Bandar Lampung. Jenis penelitian menggunakan kuantitatif, rancangan penelitian survey analitik dengan pendekatan cross sectional. Populasi dan Sampel dalam penelitian ini adalah perawat di Rumah Sakit Pertamina Bintang Amin  Bandar Lampung 103 perawat dan digunakan dengan rumus slovin sehingga didapat n = 81,9 responden dan dibulatkan menjadi 82 responden, teknik sampling menggunakan purposive sampling. Analisa data menggunakan univariat dan bivariat menggunakan chi square. Sebagian besar kinerja perawat dengan kategori kurang baik Hasil analisa data menggunakan uji chi square didapat nilai p-value = 0,000 ( α 0,05) yang artinya ada hubungan kepemimpinan dengan kinerja perawat di Rumah Sakit Pertamina Bintang Amin. Hasil analisa data menggunakan uji chi square didapat nilai p-value = 0,000 ( α 0,05) yang artinya ada hubungan desain pekerjaan dengan kinerja perawat di Rumah Sakit Pertamina Bintang Amin. Kata Kunci: Kepemimpinan, Kinerja Perawat, Rumah Sakit